Evaluation of Natural Lighting in the Lecture Room of the Graduate School of Syiah Kuala University - Ramadani, Dinda; Zahriah, Zahriah; Priandi, Riza (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2025)
The Graduate School of Syiah Kuala University consists of five main buildings, one of which is Building B. Building B serves as a space for educational activities at the master's (S2) and doctoral (S3) levels. Based on observations, Building B features windows (openings) of very large dimensions, with the building and window orientations facing west and east. This condition results in excessive and glaring natural lighting, causing thermal discomfort. Consequently, the rooms are often used with curtains, artificial lighting such as lamps, and tinted glass windows, specifically ray-band glass. This study aims to evaluate the natural lighting levels in lecture rooms based on the Indonesian National Standard (SNI No. 6197-2020). Data collection was conducted using a quantitative method, obtained through direct visual observations and field measurements, including openings, building dimensions, and illumination levels measured with a Lux Meter. The measured illumination values were then analyzed based on the SNI No. 6197-2020 standard and the observational results, enabling the identification of factors affecting natural lighting intensity. The findings indicate that the natural lighting levels within the building do not meet the SNI 6197-2020 standard for classrooms, which is 350 Lux. The average illumination value measured using the Lux Meter was 109.69 Lux.